2020
DOI: 10.3233/jnd-200508
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Type 1 Spinal Muscular Atrophy in a Series of Argentinian Children

Abstract: Background: SMA1 natural history is characterized by early development of chronic respiratory failure. Respiratory interventions in type 1 SMA infants are subject to great practice variability. Nusinersen, has been recently approved in Argentina. The advent of novel treatments has highlighted the need for natural history studies reporting disease progression in type 1 SMA. Objective: To analyze the progression, respiratory interventions and survival based on the type of respiratory support in type 1SMA patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…Age at onset critically impacts survival outcomes in patients with SMA. Our findings indicated onset ages of 3.2 months for SMA type 1, 11.1 months for type 2, and 4.3 years for type 3, consistent with prior studies on SMA types 1 and 2 [ 12 , [20] , [22] , [23] [ 24 ]]. However, our results for SMA type 3 diverged, potentially due to our smaller cohort.…”
Section: Discussionsupporting
confidence: 91%
“…Age at onset critically impacts survival outcomes in patients with SMA. Our findings indicated onset ages of 3.2 months for SMA type 1, 11.1 months for type 2, and 4.3 years for type 3, consistent with prior studies on SMA types 1 and 2 [ 12 , [20] , [22] , [23] [ 24 ]]. However, our results for SMA type 3 diverged, potentially due to our smaller cohort.…”
Section: Discussionsupporting
confidence: 91%
“…Respiratory complications are one of the most serious risks of mortality in SMA type 1 patients (27). We found that the peak time of severe respiratory complications (hospitalization required) was 3-6 months in SMA 1a, 7-12 months in SMA 1b, and 1-3 years in SMA 1c, mimicking one report from Argentinian in 2020 (28), which was mainly consistent with the survival situation in SMA type 1 patients. A high proportion of severe respiratory complications was observed; however, an assistant coughing machine and ventilation were not widely accepted in SMA type 1 patients.…”
Section: Discussionsupporting
confidence: 87%
“…SMA of type 1 is more severe, and both the age at death and the number of people using ventilators are respectively earlier and more than those in other SMA types. 1,10 Most children with SMA type 1 over two years of age need tracheotomy or all-day noninvasive ventilation for survival. 11 Children with type 2 have a progressive decline in overall function and need noninvasive ventilation from five to thirteen years old.…”
Section: Discussionmentioning
confidence: 99%